Long non-coding RNA (lncRNA) CDKN2A-DT promotes proliferation, migration, and invasion of oral squamous cell carcinoma via the PI3K/AKT/mTOR axis - Liao, Ke; Lv, Wei; Feng, Binghua; Su, Xiaoping; Huang, Xuanping (Translational Cancer Research, 2026)
CDKN2A-DT is a long non-coding RNA (lncRNA) located on chromosome 9 that plays a critical regulatory role in various malignancies, including ovarian cancer and lung cancer. However, its involvement in oral squamous cell carcinoma (OSCC) and the underlying molecular mechanisms remain poorly characterized. This study aims to investigate the expression profile, functional roles, and molecular mechanisms of lncRNA CDKN2A-DT in OSCC.